MULTICULTURAL-BASED EDUCATION AS AN EFFORT OF CONFLICT PREVENTION FOR CIDAYUMA SOCIETY IN SINGKAWANG - Marhayani, Dina Anika; Kariadi, Dodik; Yanti, Lily (Universitas Pendidikan Ganesha, 2017)
Singkawang is a multicultural city. Singkawang community famous multiethnic society consisting of Chinese, Dayak, Malay, and Madura (Cidayuma). The existence of ethnic diversity can cause various problems, such as conflicts, violence, separatism, and the loss of a sense of humanity to always respect the rights of others. Multicultural education should facilitate the learning process that transforms prejudice and all forms of discrimination to the perspective to appreciate the diversity and differences. This journal has been reviewing the literature of the same journal with articles on multicultural education. The first part of this study will introduce Cidayuma society, along with the conflicts that have occurred, and the introduction of multicultural education. The second part will discuss the importance of education-based multicultural conflict prevention for the community Cidayuma. Finally, the last part of this article will describe efforts to prevent conflict through community-multicultural based education Cidayuma in Singkawang.